Digital Media as a Cultural Stage: From Users to Reflective Inhabitants in the Context of Contemporary Indonesia - Rustini Floranita; Diana Maharani; Thomas Tokan Pureklolon (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study reexamines the position of digital media within the horizon of contemporary Indonesian culture. Digital media can no longer be adequately understood as a mere technical instrument for information exchange; rather, it must be recognised as a cultural stage upon which human beings dwell, negotiate meaning, construct identity, and contest power. Departing from Tokan Pureklolon’s (2025) framework on media and the digital public sphere, and through a critical dialogue with the works of Castells (2010), Foucault (1980), van Dijk (2013), and Pariser (2011), this research employs a qualitative literature review combined with a case study approach on contemporary Indonesian digital phenomena, including the #ReformasiDikorupsi (2019) and #GejayanMemanggil (2019) movements, the polarisation pattern across the 2014–2024 presidential election cycles, the controversial provisions of the ITE Law, and the transnational activism of Indonesia’s K-Pop fandom communities. The findings suggest that cultural transformation within Indonesia’s digital space cannot be reduced to a technological shift; it is, rather, an ontological shift from the position of user to that of inhabitant - a dweller who resides in and is morally engaged with the digital socio-cultural ecosystem. The novelty of this study lies in the formulation of the Triadic Reflective Framework of Digital Culture (TRF-DC), which synthesises the three pillars of digital culture - meaning production, identity formation, and power relations - with an ethical-reflective layer as the ontological precondition of digital citizenship. The study further proposes the concept of the Reflective Inhabitant as a normative model for the Indonesian digital citizen, integrating technical skill, critical literacy, and ethical consciousness within a single, culturally grounded framework.